One lung ventilation in a patient with an upper and lower airway abnormality - Kaza, Sangita R (Medknow Publications & Media Pvt Ltd, 2012)
One-lung ventilation for a thoracotomy procedure was achieved with the help of a endobronchial blocker in a young girl with limited mouth opening, minimal neck extension, and a distorted tracheo-bronchial anatomy. As the patient would not cooperate for an awake nasotracheal intubation despite adequate preperation, an inhalational anesthetic was used to make the patient unconscious, taking care that spontaneous breathing was maintained. Nasotracheal intubation was done with the help of a fiberoptic bronchoscope. A wire-guided Arndt endobronchial blocker was placed coaxially through the endotracheal tube using a fiberoptic bronchoscope. This case report highlights that in a scenario of both upper and lower airway distortion, a bronchial blocker positioned through a nasotracheal tube under fiberoptic guidance might be the best option when one-lung ventilation is required.